Pengaruh Literasi Keuangan Persepsi Kemudahan dan Kepercayaan Terhadap Perilaku Penggunaan Sistem Pembayaran Digital QRIS Pada Mahasiswa FEB UNISRI - Hijjatul Nur Wakhidah; Rispantyo Rispantyo (Pusat Riset dan Inovasi Nasional, 2026)
This research seeks to examine how financial knowledge, the perceived simplicity of use, and trust impact the adoption of the Quick Response Code Indonesian Standard (QRIS) digital payment system by students at the Faculty of Economics and Business, Slamet Riyadi University Surakarta. A quantitative method is utilized in this study, involving primary data that was gathered through surveys distributed to FEB UNISRI students who are knowledgeable about and have previously utilized QRIS. The sampling method used was purposive sampling, which included a total of 100 student participants. The collected data was evaluated with multiple linear regression analysis through the SPSS software, following validity assessments, reliability assessments, and classical assumption evaluations. The findings reveal that financial literacy, perceived ease of use, and trust positively and significantly influence the behavior associated with QRIS usage. These results imply that increased financial literacy, enhanced perceived ease of use, and more robust trust in digital payment systems result in a higher frequency of QRIS usage among students in their everyday transactions. This study is anticipated to aid in advancing digital financial literacy and serve as a valuable reference for relevant parties in encouraging the uptake of cashless payment solutions among university students